Teacher Appraisers' Perceptions of Teacher Appraisal - Ahmed Hamid Abdulrazzaq (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2022)
This study investigates teacher appraisers' perceptions of teacher appraisal in terms of its purpose, methods, and criteria. Fourteen teacher-appraisers were administered semi-structured interviews to gain an in-depth understanding of their perceptions of appraisal. Analysis of the responses revealed that participants seemed to advocate the use of teacher appraisal for both professional improvement and decision-making purposes. Participants also seemed to agree about the value of classroom observation as an objective method of evaluation. Still, they were divided regarding the use of student evaluation, student achievement, and other indi-rect observation methods, especially for decision-making purposes. As for evaluation criteria, the results revealed that while teacher-appraisers paid attention to all aspects of the teaching process in their evaluation, their focus remained mainly on those skills exhibited during the actual delivery of teaching.